Fabrication and Characterization of Sensitive Room Temperature NO2 Gas Sensor Based on ZnSnO3 Thin Film. Issue 16 (21st June 2019) - Dabbabi, Samar; Nasr, Tarek Ben; Madouri, Ali; Cavanna, Antonella; Garcia‐Loureiro, Antonio; Kamoun, Najoua
Abstract : In this work, the simple and low cost fabrication of a new sensitive gas sensor ZnSnO3 thin film is demonstrated by mixing doped oxide solutions based on tin doped zinc oxide (ZnO:Sn) and fluorine doped tin oxide (SnO2 :F). The structural, morphological, and optical properties are characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), and spectrophotometry, respectively. Structural and morphological analysis confirmed the deposition of ZnSnO3 film with porous surface using mixed doped oxide solutions. Optical studies reveal that ZnSnO3 film exhibits a high transmittance (85%) and a wide band gap energy (3.5 eV), larger than that of ZnO:Sn film. Moreover, the several benefits of ZnSnO3 film are confirmed by offering high sensitivity to NO2 at room temperature. Abstract : In the present work, a new sensitive gas sensor ZnSnO3 thin film is obtained by mixing doped oxide solutions based on tin doped zinc oxide (ZnO:Sn) and fluorine doped tin oxide (SnO2 :F). Meanwhile, the structural, optical, and electrical properties of the thin films are studied. The results reveal that the ZnSnO3 film is highly sensitive to NO2 at room temperature.